2021
DOI: 10.1177/03611981211052026
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Materials: A Review of Recycled Concrete Aggregate Utilization as Pavement Material

Abstract: In this paper, a comprehensive literature review was conducted on the utilization of recycled concrete aggregate (RCA), which is the dominant construction and demolition waste material, in base and subbase layers and its comparison with natural aggregate (NA). The effects of crushing on the particles as a result of the compaction on the resilient modulus, permanent deformation, and California Bearing Ratio are analyzed. The paper also contains the NA consumption and waste disposal policies of different countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 90 publications
4
17
0
Order By: Relevance
“…Some studies have been carried out to evaluate and compare the properties of natural granular layers vs. granular layers with RCA replacements. From the results reported in the literature regarding mechanical properties such as the California Bearing Ratio (CBR) and the LA abrasion test, it has been determined that RCAs are comparable to NA [14], highlighting that lower strengths and higher abrasions are observed but they fulfill the standards for GSB. In terms of resilient modulus, it has been established that GB with RCA show higher results than natural aggregates [14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have been carried out to evaluate and compare the properties of natural granular layers vs. granular layers with RCA replacements. From the results reported in the literature regarding mechanical properties such as the California Bearing Ratio (CBR) and the LA abrasion test, it has been determined that RCAs are comparable to NA [14], highlighting that lower strengths and higher abrasions are observed but they fulfill the standards for GSB. In terms of resilient modulus, it has been established that GB with RCA show higher results than natural aggregates [14].…”
Section: Introductionmentioning
confidence: 99%
“…From the results reported in the literature regarding mechanical properties such as the California Bearing Ratio (CBR) and the LA abrasion test, it has been determined that RCAs are comparable to NA [14], highlighting that lower strengths and higher abrasions are observed but they fulfill the standards for GSB. In terms of resilient modulus, it has been established that GB with RCA show higher results than natural aggregates [14]. In addition, they found that RCA had better mechanical properties than NA but had higher permanent deformation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations